On the Fekete-Szegö Inequalities of the Generalized Mittag-Leffler Function Associated with a Lambert Series (Contemporary Mathematics, 2024)
This study aims to investigate the Fekete-Szegö problem for the linear operator generated by the convolution (the Hadamard product) involving one of the generalized forms of the Mittag-Leffler function and the well-known Lambert series. The findings will mainly apply on some subclasses of starlike and convex functions.
Keywords: fekete-szegö problem; mittag-leffler function; hadamard product; linear operator; lambert series; starlike and convex functions